PENGARUH PEMBERIAN INSENTIF, BEBAN KERJA DAN DISIPLIN TERHADAP KINERJA KARYAWAN PADA PT BPR PERBAUNGAN HOMBAR MAKMUR PERBAUNGAN - Simangunsong, Elisabeth; Manihuruk, Citra Adelia; Haloho, Elizabeth; Bangun, Kristina (LPPM Universitas Katolik Santo Thomas Medan, 2024)
This research aims to determine and analyze the effect of providing incentives, workload and discipline on employee performance at PT BPR Perbaungan Hombar Makmur Perbaungan. The population of this study was 32 people and the number of samples using saturated sampling techniques or census was 32 people. The data analysis technique used in this research is analysis with the SmartPLS 4 SEM model. The results of the research show that the incentive variable has a positive and significant effect on employee performance with an original sample of 0.456 and a t-statistic test value of 3.808 > t table 1.701 and a p value of 0.000 < 0. 05. Workload has a negative and significant effect on employee performance with an original sample value of -0.686 and a t-statistic test of 4.924 > t table 1.701 with a p value of 0.000 < 0.05. Discipline has a positive and significant effect on employee performance with an original sample value of 0.411 and a tstatistics test of 3.960 > ttable 1.701 with a p value of 0.000 < 0.05. The R Square value of 0.750 is equal to 73%. So it can be explained that variations in employee performance can be explained by independent variables, namely incentives, workload and discipline, amounting to 73%, the remaining 27% is explained by other factors not explained in the research.